Foraging behaviour, swimming performance and malformations of early stages of commercially important fishes under ocean acidification and warming - Pimentel, Marta S.; Faleiro, Filipa; Marques, Tiago A.; Bispo, Regina; Dionísio, Gisela; Faria, Ana M.; Machado, Jorge; Peck, Myron A.; Pörtner, Hans; Pousão-Ferreira, Pedro; Gonçalves, Emanuel J.; Rosa, Rui (Climatic Change, 2017)
The Portuguese Foundation for Science and Technology (FCT) supported this study through doctoral grants to M.S.P. and G.D. (SFRH/BD/81928/2011 and SFRH/BD/73205/2010, respectively), a post-doc grant to F.F. (SFRH/BPD/79038/2011), and project grants to P.P.F. (AQUACOR-PROMAR31-03-05FEP-003) and R.R. (PTDC/MAR/0908066/2008 and PTDC/AAGGLO/3342/2012). Early life stages of many marine organisms are being challenged by climate change, but little is known about their capacity to tolerate future ocean conditions. Here we investigated a comprehensive set of biological responses of larvae of two commercially important teleost fishes, Sparus aurata (gilthead seabream) and Argyrosomus regius (meagre), after exposure to future predictions of ocean warming (+4 °C) and acidification (ΔpH = 0.5). The combined effect of warming and hypercapnia elicited a decrease in the hatching success (by 26.4 and 14.3 % for S. aurata and A. regius, respectively) and larval survival (by half) in both species. The length for newly-hatched larvae was not significantly affected, but a significant effect of hypercapnia was found on larval growth. However, while S. aurata growth was reduced (24.8–36.4 % lower), A. regius growth slightly increased (3.2–12.9 % higher) under such condition. Under acidification, larvae of both species spent less time swimming, and displayed reduced attack and capture rates of prey. The impact of warming on these behavioural traits was opposite but less evident. While not studied in A. regius, the incidence of body malformations in S. aurata larvae increased significantly (more than tripled) under warmer and hypercapnic conditions. These morphological impairments and behavioural changes are expected to affect larval performance and recruitment success, and further influence the abundance of fish stocks and the population structure of these commercially important fish species. However, given the pace of ocean climate change, it is important not to forget that species may have the opportunity to acclimate and adapt. ...